PERUBAHAN STRUKTUR EKONOMI DAN KESEMPATAN KERJA SERTA KUALITAS SUMBERDAYA MANUSIA DI INDONESIA - KARIYASA, KETUT (SOCA: Jurnal Sosial Ekonomi Pertanian, 2012)
The result of Assessment on “Changes of Economic and Employment Structure as well as Quality of Human Resource in Indonesia” showed that in 1995 – 2001 periods economic (GNP) structure in Indonesia has been changed from S-I-A (Services-Industry- Agriculture) pattern to I-S-A pattern. Meanwhile, during the same period employment structure was remain stable, namely A-S-I pattern. The unbalanced changes between economic and employment structures were predicted to be the factors causing labor productivity and society welfare in agricultural sector were declining. In agricultural sector itself the absorption of labor force was dominated by food crops sub sector. There was a quality improvement in human resource. However, the problem is government capability to create employment was not sufficient to provide job opportunity for improved human resource.
Keywords: Changes, Structure, Economic, Employment, and Human Resource.